SEJARAH DAN PERKEMBANGAN TARI ENTARAI PADA SUKU DAYAK KETUNGAU SESAEK DI KECAMATAN SEKADAU HILIR - Putri, Meitika Kaping; Ismunandar, Ismunandar; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is motivated lack of writing and documenting of traditional dancing in the local area. The researcher very excited toward dayak culture especially about Entrai dance to know the history and development about it’s.The method used in this research is historis descriptive, in the from of qualitative research by multidisciplinary approach that divided into three of theories, those are the theory of history, anthropology, and sociology. Tools of data collecting were taken by several techniques such as observation, interview, and documentation techniques from the statements of some artists of Entarai Dancing as the informants. The validity techniques were extending the observation and source triangulation technique that combined the statements from the informants.The history of Entarai Dancing started in 1960, where Juyah, an indigenous of Ketungau Sesaek Dayak Tribe, as the creator of the first Entarai Dancing. Then, Libau introduced and developed that in 1987 as the first dancer of Entarai Dancing. In 1996, Entarai Dancing developed by Aki in the Inauguration of St. Gelma Galgani Church. In 2000 until now, Entarai Dancing use in entertain dancing. The structure of gestures in Entarai Dancing divided into three parts, those are respect, main, and closing gestures. The result of this research was expected to implement in Art of Culture lesson in the first semester of Grade Eight. Keywords: History and development, Entarai